Hubungan Pendapatan Keluarga dan Pemberian MP ASI dengan Kejadian Stunting di Wilayah Kerja Puskesmas Manggasa Makassar - Hafdaniar, Hafdaniar; Hasriani, Siti; Asnuddin, Asnuddin (Jurnal Sains, Teknologi dan Kesehatan, 2024)
Stunting is the nutritional status of toddlers which is based on the height index for age. Various aspects can influence the high incidence of stunting, including education, social culture, pregnancy history, exclusive breastfeeding, provision of complementary foods, health services, family income, economics, political environment and others. The aim of this research is to determine the relationship between family income and provision of MP ASI on the incidence of stunting at the Manggasa Community Health Center. This type of research is quantitative analytical with a case control design using a retrospective approach. The population in this study were all toddlers aged 2-3 years who lived in the working area of ​​the Manggasa Health Center, Makassar City in November-December 2023, totaling 60 people. The sampling technique uses Simple Random Sampling. The results of statistical tests using Chi-Square show that there is a relationship between family income and the incidence of stunting where the p-value is (0.002) and there is a relationship between giving MP ASI and the incidence of stunting where the p-value is (0.004). There is a need to increase education regarding nutrition in children's growth and development, providing training on processing nutritious food without requiring a lot of money